MENUJU PARADIGMA DEMOKRASI YANG BERKUALITAS DALAM IMPLEMENTASI KEHIDUPAN POLITIK DI INDONESIA - Awaliyah, Siti (JURNAL KONSTITUSI, 2011)
Indonesia represents state embracing democracy system, in its growth always experience of ebb, till finally reform expected as early repair of life of democracy in Indonesia. Existence of area autonomy commending Election of Regional Leader and Proxy Regional Leader directly represents one of the form executions of democracy.Â